Selective adsorption of cationic dye utilizing poly (methacrylic acid-co-ethylene dimethacrylate) monolith from wastewater - Bessy D’Cru; Mohamed O. Amin; MetwallyMadkour; Entesar Al-Hetlani (Kuwait Journal of Science)
In this study, poly(methacrylic acid-co-ethylene dimethacrylate (poly(MAA-co-EDMA)) monolith was prepared for the selective adsorption of acidic dye namely methylene blue (MB) from wastewater. The fabrication of the monolith was carried out by photoinitiation polymerization by irradiating a mixture methacrylic acid (MAA), ethylene dimethacrylate (EDMA), porogenic solvents and an initiator. Batch adsorption assays were performed to examine the impact of monolith dosage and initial dye concentration on the adsorption capacity and efficiency of the monolith towards MB dye molecules. Adsorption kinetic study revealed that MB adsorption on the monolith followed pseudo-second-order model and equilibrium adsorption behavior was best modeled by Langmuir adsorption isotherm with a maximum adsorption capacity of 50.00 mg g-1. Owe to the presence of negative binding sites on the monolith, cationic MB molecules are selectively adsorbed from MB/MO mixture with adsorption efficiency of 99.54% at equilibrium time. Finally, the monolith effectively adsorbed MB from the tap water in presence of competing ions and the maximum adsorptive capacity obtained was 47.62 mg g-1 with 84.5% adsorption efficiency. Hence, poly(MAA-co-EDMA) monolith is an adequate sorbent for the treatment of cationic dyes in the presence of other dyes and competing ions from wastewater.